Virgin Mother Goddesses of Antiquity - Rigoglioso, M. author. aut Link
XI, 267 p.
Keywords: This study of various female deities of Graeco-Roman antiquity is the first to provide evidence that primary goddesses were conceived of as virgin mothers in the earliest layers of their cults. By taking feminist analysis of divinities further, this book provides a fresh angle on our understanding of these deities.